2017
DOI: 10.4103/0971-3026.202955
|View full text |Cite|
|
Sign up to set email alerts
|

Radiofrequency ablation of osteoid osteoma in common and technically challenging locations in pediatric population

Abstract: Context:Percutaneous radiofrequency ablation (RFA) of osteoid osteoma has a high technical and clinical success rate. However, there is limited data on its use in the pediatric population, especially in technically challenging locations.Objective:To assess the safety and efficacy of computed tomography (CT)-guided percutaneous RFA of osteoid osteoma in pediatric population.Patients and Methods:From June 2009 to May 2014, 30 patients with osteoid osteoma were treated with CT-guided RFA in common (25 cases) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…They concluded that RFA is a safe and highly effective modality of treatment in the pediatric population, even in technically difficult locations. 2 Our patient has benefitted immensely from this minimally invasive intervention following a failed conservative management.…”
Section: Discussionmentioning
confidence: 92%
“…They concluded that RFA is a safe and highly effective modality of treatment in the pediatric population, even in technically difficult locations. 2 Our patient has benefitted immensely from this minimally invasive intervention following a failed conservative management.…”
Section: Discussionmentioning
confidence: 92%
“…Percutaneous RFA-treatment is an outpatient procedure that does not require large dissections or bone excisions. This makes percutaneous interventional treatments advantageous 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 17, 18, 20, 21. Since the most of our patients were admitted from far-cities, we hospitalised them for one night for close follow-up of possible complications.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that CT-guided percutaneous RFA is beneficial and may be preferred for treatment of OO 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14. The purpose of this study is to report the efficacy and safety of RFA-treatment in OO in a cohort of large number of cases.…”
Section: Introductionmentioning
confidence: 99%
“…34 Treatments for osteoid osteoma range from surgical treatment, such as curettage, to minimally invasive techniques, such as radiofrequency ablation. 35 Four patients at our institution were treated with curettage, followed by PMMA bone filler in 1 patient, and 1 patient underwent excision. The patient who received the PMMA bone filler recurred after 3 months and underwent repeated curettage of the lesion followed by repacking with PMMA.…”
Section: Bone Tumorsmentioning
confidence: 99%